Synthesis of active hybrid films reinforced with cellulose nanofibers as active packaging material - Wan Yahaya, Wan Amnin; Subramaniam, Sarmilaah Dewi; Mohd Azman, Nurul Aini; Almajano, Maria Pilar; Adam, Fatmawati (Wiley, 2022)
Active packaging films derived from renewable biopolymers with an antioxidant formulation are a promising alternative in prolonging food shelf life. This study aimed to develop active hybrid films from semi-refined carrageenan, plasticized with glycerol, incorporating α-tocopherol, and enhanced with cellulose nanofibers derived from empty fruit bunch as reinforcing agents for improved film function in active packaging. The active hybrid films were characterized for their properties, and the release of antioxidant α-tocopherol was observed in food simulant and fresh meat. The application of the active hybrid films reinforced with cellulose nanofibers as active packaging for food products is presented.